Effect of atmospheric and sea stability on liquefied natural gas (LNG) dispersion: Implications to Australian LNG marine transport - Ikealumba, Walter; Wu, Hongwei (Elsevier Ltd, 2017)
© 2017 Elsevier LtdIncreasing demand for natural gas as a fuel source has led to increasing marine transport of liquefied natural gas (LNG) that is flammable and makes LNG tankers a potential terrorist target. This study utilises CFD simulation coupled with wave modelling for investigating the effect of atmospheric and sea (sea waves in particular) stability on LNG pool formation and dispersion process. Pasquill stability was used to determine the stability classes for each of the scenarios and cases studied. The importance of modelling the roll and pitch of LNG carriers was investigated; with sloshing leading to an increase of up to 31% on tank wall pressure and an increase of 100 s on spill time. Analyses also show that as stability increases, LNG pool radius also increase; and a larger pool radius was indicative of a lower evaporation rate. The increasing stability (more stable conditions) was shown to have little effect on the earlier growth of the LNG pool and the temporal evolution of evaporation rate (0–50 s); once the discharge of LNG form the tanker starts decreasing, the effect of increasing stability in each case, starts becoming visible (~50 and onwards). The results showed that stability effects induced by the sea waves were noted to have a greater impact on the whole spill and dispersion process. Overall the increasing stability conditions led to 8% increase in downwind dispersion of the vapour cloud, 11% increase in the crosswind dispersion and 19% decrease in vertical dispersion. Finally the implications of this study to Australian LNG export was investigated, from which it was concluded that LNG exports during winter can lead to the least affected areas compared to that in summer. In order to mitigate LNG spill hazards from an LNG carrier, the areas of focus should be on travel routes in close proximity to islands; and following an LNG spill, stopping the LNG carrier would minimise the hazard zone.